2012
DOI: 10.1152/ajpregu.00313.2012
|View full text |Cite
|
Sign up to set email alerts
|

Temporal organization of activity in the brown bear (Ursus arctos): roles of circadian rhythms, light, and food entrainment

Abstract: September 12, 2012; doi:10.1152/ajpregu.00313.2012.-Seasonal cycles of reproduction, migration, and hibernation are often synchronized to changes in daylength (photoperiod). Ecological and evolutionary pressures have resulted in physiological specializations enabling animals to occupy a particular temporal niche within the diel cycle leading to characteristic activity patterns. In this study, we characterized the annual locomotor activity of captive brown bears (Ursus arctos). Locomotor activity was observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
55
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 76 publications
9
55
0
1
Order By: Relevance
“…Actogramformatted data have been used previously in wild animals to examine temporal activity patterns on a fine scale and to reveal the operation of a circadian clock (Van Oort et al 2004. Our own published work has confirmed a high concordance between observer identified (video recorded) and actogramformatted activity data in captive grizzly bears (Ware et al 2012). Actograms were double-plotted to better visualize day : night transitions and niche switches.…”
Section: Methodsmentioning
confidence: 65%
See 1 more Smart Citation
“…Actogramformatted data have been used previously in wild animals to examine temporal activity patterns on a fine scale and to reveal the operation of a circadian clock (Van Oort et al 2004. Our own published work has confirmed a high concordance between observer identified (video recorded) and actogramformatted activity data in captive grizzly bears (Ware et al 2012). Actograms were double-plotted to better visualize day : night transitions and niche switches.…”
Section: Methodsmentioning
confidence: 65%
“…Given the importance to bears of attaining a large body mass prior to hibernation, food entrainment may play an important role in shaping their behavior. In support of this hypothesis, we have recently shown that a switch to nighttime feeding of captive grizzly bears causes a switch to nocturnal activity despite concurrent exposure to natural daylight (Ware et al 2012).…”
mentioning
confidence: 67%
“…Bear activity during the active season and hibernation was monitored with Actical™ physical activity monitors (Phillips Respironics, Bend, Oregon, USA) encased in aluminum protective cases and glued to the skin with two-part epoxy at the shoulder (Ware et al 2012). Application and removal of the Acticals was performed on bears trained to remain still for a food reward.…”
Section: Activity Monitorsmentioning
confidence: 99%
“…RPS18 was used as a reference gene primarily limited to in vivo studies. Bear hibernation behavior and numerous aspects of their physiology have been described (Craighead and Craighead 1972;Hellgren 1998;Nelson 1973Nelson and Robbins 2010;Ware et al 2012). Information on foraging behavior (Farley and Robbins 1995;Lopez-Alfaro et al 2013;Robbins et al 2012b) and the distinct phases of weight change throughout the year was presented by Nelson et al (1983), Hilderbrand et al (1999), and Schwartz et al (2003).…”
Section: Plin2mentioning
confidence: 99%
“…Different combinations of individuals were used in each experiment. Bears were anesthetized using the protocol described in Ware et al (2012). Biopsy sites were shaved and surgically prepared using chlorhexidine and 70 % ethanol.…”
Section: Introductionmentioning
confidence: 99%